IGF-I Influences Everolimus Activity in Medullary Thyroid Carcinoma - Gentilin, Erica; Di Pasquale, Carmelina; Rossi, Martina; Tagliati, Federico; Gagliano, Teresa; Rossi, Roberta; Pelizzo, Mariarosa; Merante Boschin, Isabella; degli Uberti, Ettore C.; Zatelli, Maria Chiara (Frontiers in Endocrinology, 2015)
Context: Medullary thyroid carcinoma (MTC) is a rare tumor originating from thyroid parafollicular C cells. It has been previously demonstrated that IGF-I protects MTC from the effects of anti-proliferative drugs. Everolimus, an mTOR inhibitor, has shown potent anti-proliferative effects in a human MTC cell line, TT, and in two human MTC primary cultures Objective: To verify whether IGF-I may influence the effects of Everolimus in a group of human MTC primary cultures. Design: We collected 18 MTCs that were dispersed in primary cultures, treated without or with 10 nM - 1 M Everolimus and/or 50 nM IGF-I. Cell viability was evaluated after 48 h and Calcitonin (CT) secretion was assessed after a 6 h incubation. IGF-I receptor downstream signalling protein expression profile was also investigated. Results: Everolimus significantly reduced cell viability in 8 MTC (by ~20%; P<0.01 vs. control; E-R MTCs), while cell viability did not change in 10 MTCs (E-NR MTCs). In E-R MTCs IGF-I blocked the antiproliferative effects of Everolimus, that did not affect CT secretion, but blocked the stimulatory effects of IGF-I on this parameter. IGF-I receptor downstream signalling proteins were expressed at higher levels in E-NR MTC as compared to E-R MTCs. Conclusions: IGF-I protects a sub-set of MTC primary cultures from the antiproliferative effects of Everolimus and stimulates CT secretion by an mTOR mediated pathway, that, in turn, may represent a therapeutic target in the treatment of aggressive MTCs.